CP-154,526: a potent and selective nonpeptide antagonist of corticotropin releasing factor receptors. - Schulz, D W (1996)
Here we describe the properties of CP-154,526, a potent and selective nonpeptide antagonist of corticotropin (ACTH) releasing factor (CRF) receptors. CP-154,526 binds with high affinity to CRF receptors (Ki < 10 nM) and blocks CRF-stimulated adenylate cyclase activity in membranes prepared from rat cortex and pituitary. Systemically administered CP-154,526 antagonizes the stimulatory effects of exogenous CRF on plasma ACTH, locus coeruleus neuronal firing and startle response amplitude. Potential anxiolytic activity of CP-154,526 was revealed in a fearpotentiated startle paradigm. These data are presented in the context of clinical findings, which suggest that CRF is hypersecreted in certain pathological states. We propose that a CRF antagonist such as CP-154,526 could affirm the role of CRF in certain psychiatric diseases and may be of significant value in the treatment of these disorders.